Curricular and Extracurricular Learning among Students with Resilience Potential. Social Inequalities in Higher Education - Ceglédi, Tímea; Dabney-Fekete, Ilona Dóra (Central European Journal of Educational Research, 2023)
Does resilience potential in higher education mature into success or does it remain merely a promise of success due to rising social inequality? We studied curricular and extracurricular learning of students with outstanding academic achievement who entered higher education despite their disadvantage of social background (= students with resilience potential). A student survey database compiled in the research project “Higher Education for Social Cohesion – Cooperative Research and Development in a Cross-border Area” (HERD) (HURO/0901/253/2.2.2.) in 2012 was analyzed. Students of three Eastern Hungarian higher education institutions were surveyed (N = 1205). Students with resilience potential were identified in the intersection of two groups of variables: social background and input academic achievement. We have conducted a cluster analysis, which has resulted in the identification of students with resilience potential and other researched groups: drifters (low social background and low input academic achievement), beneficiaries (high social background and high academic achievement) and indifferent prodigals (high social background and low academic achievement). To sum up our results, the students with resilience potential only use higher education to fulfill curricular requirements, and hit a ceiling, compared to the beneficiaries, when it comes to the student year mining, meaningful extracurricular activities. Thus social inequalities crawl through these invisible channels into higher education and beyond.